Trend and prediction of the disease burden of carbon monoxide poisoning in China - Chaocheng WANG; Xinyun DUAN; Yu DU (环境与职业医学)
BackgroundAcute carbon monoxide poisoning is now one of the major causes of morbidity and mortality in occupational and non-occupational poisoning in China, and become a serious public health problem. Understanding the current and predicting the future disease burden of carbon monoxide poisoning are essential for adopting effective disease prevention and control strategies in the future.ObjectiveTo understand the burden of disease of carbon monoxide poisoning in China from 1990 to 2019 and predict the trend of morbidity and mortality in the following decade to provide a scientific basis for the prevention of carbon monoxide poisoning in China.MethodsThe incidence, mortality and disability-adjusted-life-years (DALYs) rates of carbon monoxide poisoning in China from 1990 to 2019 were extracted from the Global Burden of Disease Database (GBD2019). Time trend analysis of the burden of disease for carbon monoxide poisoning was performed using Joinpoint 5.0.2 software, and annual percentage change (APC) and average annual percentage change (AAPC) and their 95%CIs were calculated. Bayesian age-period-cohort model (BAPC) and Nordpred age-period-cohort model were used in R 4.3.3 to predict the disease burden of carbon monoxide poisoning among Chinese residents in 2020—2029.ResultsAn overall increasing trend of the age-standardized incidence rate of carbon monoxide poisoning in China from 1990 to 2019 was observed and AAPC=1.05%, of which the AAPC for women was 0.90% and that for men was 1.16%. An overall decreasing trend of the age-standardized mortality rate and age-standardized DALYs from 1990 to 2019 was observed and the AAPC for males or females was <0. the results of the BAPC model expected that an increasing trend from 2020 to 2029 in age-standardized morbidity rate (females: 18.85/100 000 in 2020 to 19.12/100,000 in 2029; males: 22.51/100 000 in 2020 to 22.60/100 000 in 2029); and a decreasing trend in age-standardized mortality rate (females: 0.70/100,000 in 2020 to 0.52/100 000 in 2029; males: 1.13/100 000 in 2020 to 0.97/100 000 in 2029). The results of the Nordpred age-period-cohort model showed similar trends, suggesting that the results were stable.ConclusionCarbon monoxide poisoning caused a serious burden of disease in the Chinese population during the period 1990—2019, with adolescents and middle-aged and elderly people being the most affected groups. Subsequent projections have shown an upward trend in age-standardized incidence rates and numbers of cases, so we still need to deepen the implementation of prevention and treatment of the occurrence and development of carbon monoxide poisoning, and to reduce the harm it causes to the population.